2018
DOI: 10.3390/pharmacy6020029
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Knowledge, Attitude and Barriers towards Pharmacovigilance among Physicians and Pharmacists of Abbottabad, Pakistan

Abstract: Objectives: Pharmacovigilance in Pakistan needs robust preference in terms of implementation and consistent movement of structured approaches. The objective of this study is to explore the knowledge, attitude and barriers towards adverse drug reaction (ADR) reporting among physicians and pharmacists and to explore the encouraging factors of ADR reporting. Methods: The current research was a cross-sectional study design in which a pre-validated questionnaire was administered to physicians and pharmacists in Abb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 39 publications
4
30
0
Order By: Relevance
“…Similar findings were reported by Joubert et al [11] in South Africa or Syed et al [20] in Pakistan where pharmacists and physicians have shown few knowledge on the concept of pharmacovigilance. These actors need information and training about pharmacovigilance.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similar findings were reported by Joubert et al [11] in South Africa or Syed et al [20] in Pakistan where pharmacists and physicians have shown few knowledge on the concept of pharmacovigilance. These actors need information and training about pharmacovigilance.…”
Section: Discussionsupporting
confidence: 89%
“…Ampadu et al [18] indicate that at the end of September 2015, individual case safety reports (ICSRs) to VigiBase represented 0.88% of global ICSRs. Under-reporting of ADRs cases, may also due to the lack of pharmacovigilance center, lack of easier reporting forms or unavailability of reporting forms as previously reported by De Briyne et al [19] in Europe and Syed et al [20] in Pakistan.…”
Section: Discussionmentioning
confidence: 95%
“…In contrast, studies from developed countries have reported that most pharmacists were well-equipped and had comprehensive knowledge about their role in pharmacovigilance, pharmaco-epidemiology, posology, and pharmaco-economics, owing to well-established guidelines and vigilant regulatory bodies [3,7,39]. Taking this into account, better knowledge about pharmacovigilance among pharmacists in Pakistan is likely to be attributable to the recent implementation of a National Pharmacovigilance Center [40].…”
Section: Discussionmentioning
confidence: 99%
“…The initial negative and neutral attitude of community pharmacists towards ADR reporting could be due to hesitation to take up the additional workload, fear of legal issues and/or monetary loss. This was evident in item A 2 regarding their interest in attending pharmacovigilance, where 87.3% of phar- (Syed et al, 2018). However, there was a signi icant improvement in pharmacist attitude towards pharmacovigilance with 90.2% feeling that they should be involved in pharmacovigilance.…”
Section: Exclusion Criterionmentioning
confidence: 96%